2 - Theorising the Relationship of Higher Education and the Public Good in Africa - Unterhalter, Elaine; Allais, Stephanie (Journal of Higher Education in Africa, 2022)
This article explores conceptualisations of the public good role of higher education and considers their application to higher education in African countries. The article starts by delineating a number of different ways in which higher education and the public good are linked, grouping these together as instrumental and intrinsic versions of the relationship between higher education and the public good. In considering the connections and disjunctures between these two formulations and the way studies on higher education in contemporary Africa have engaged with this debate, we argue for discussing the importance of processes that link or have the potential to connect instrumental and intrinsic visions of higher education and the public good. We discuss these, drawing on a set of framing ideas associated with conditions of possibility and forms of social contract, which, we argue, express a less abstract form of this discussion, more responsive to the complexities of context associ ted with actual higher education institutions and the systems they work in.